Design and fabricate of portable and multifunction shoe rack / Farez Azra'e Arman and Radzi Abdul Rasih - Arman, Farez Azra'e; Abdul Rasih, Radzi (School of Mechanical Engineering, 2023)
Shoe racks are commonly used furniture storage units available in the market, featuring various designs. Previous studies indicate that most existing products are in good working condition, providing space or seating but lacking portability. However, there is a growing demand for shoe racks that offer multiple functions. This project aims to address this need by introducing innovative ideas for foldable and multi-purpose shelves. The primary objective is to develop versatile and portable shoe racks suitable for various users, with a particular focus on students living in hostels. The project aims to utilize cost-effective and readily available materials that can be efficiently manufactured and supervised. In summary, the product is designed to help customers organize their shoes effectively and exceed their expectations, providing a delightful user experience